BLURRING BOUNDARIES: EXPLORING CHROME TANNED LEATHER AS A SCULPTURAL MEDIUM THAT MERGER PLANT FORMS WITH MATERIAL CULTURE - Ankyiah, Francis; Okae-Anti, Ernest (ISI Press Institut Seni Indonesia Surakarta, 2024)
This art-based research explored the sculptural potential of using chrome tanned leather to merge plant forms with materials culture. Chrome tanned leather was selected as the medium for its flexible yet durable qualities that allow it to be manipulated into organic shapes reminiscent of botanicals. A series of sculptural works were created using varieties of chrome tanned leather offcuts that were either stitched, glued or tucked over metal pipes, wood or plastic tube armatures. These armatures were then curled, spiralled or formed into nodule shaped components evoking leaves, vines, roots and pods. The works aimed to blur boundaries between the natural and industrial by incorporating the distinctive patina and textures of chrome tanned leather, a material intrinsically tied to industry and manufacturing. Through an iterative process, techniques for shaping, assembling and finishing the leather components were developed. Finishing techniques such as tooling, staining and distressing were employed to enhance botanical details and accentuate the unique properties of the leather. The research found that chrome tanned leather lends itself well to organic sculptural forms and allowed an imaginative merging of plant inspirations with an industrially produced material. By flexing the material past its functional limits, a hybrid language was discovered that challenges perceptions of what leather can signify as an artistic medium. The research contributes to interrogating relationships between nature, culture and materials.